Hubungan Pengetahuan terhadap Kepatuhan Minum Obat Anti Hipertensi pada Pasien Hipertensi Usia Lanjut di Puskesmas Krian Kabupaten Sidoarjo - SUKMA SAHADEWA; NOVA NOVITA; KADEK DWIPA; GEDE ABI YOGA; MANDASARI DWI PERTIWI (HANG TUAH MEDICAL JOURNAL, 2019)
Introduction: Hypertension is persistent abnormal high artery pressure. Patient with hypertension should have knowledge about the disease especially the cause, symptoms and how important to take the medicine regularly in long term periode and the dangerous if it is not taken regularly. The purpose of these study is to observe the role of The Role Of Knowledge In The Compliances For Taking Hypertension Medicine among Geriatric Patient At Krian Primary Health Care Sidoarjo District. Method : The population of the study were patient who came to geriatric clinic at Krian primary health care Sidoarjo district as much 332 patient with sampel 75 people and were analyzed using Spearman Correlation. Results: There is role of knowledge in the obediences for taking hypertension medicine among geriatric patient at Krian Primary Health Care Sidoarjo district with p< 0.05 (p = 0.000) Keywords : Knowledge, Compliances, Hypertension